HISTORY OF THE DEVELOPMENT OF BOXING AND ACHIEVEMENTS - Ataev O. R. (Galaxy International Interdisciplinary Research Journal, 2022)
This article fully covered the history of the development of Bok and the achievements made in it. The article covered the history of the development of boxing in different states and the changes that were there.